The Problem of State in the Instructional Management in Thai Classical Music Performance Skill Courses of Pipat Undergraduate Students - Meephueak, Jirayu; Laovanich, Vitchatalum (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
This research aimed to study the problem of state in the instructional management in Thai classical music performance skill courses of Pipat undergraduate students. The research employed a qualitative methodology, collecting data from interviews of key informants by purposive sampling, including six teachers and nine undergraduate students majoring in Pipat. Data were analyzed using interpretation and inductive conclusion, then presented by the descriptive method. The finding shows that the problem states consist of four aspects including 1) personality: mallet holding and sitting 2) performance: using weights, muscles, and technics, unstably rhythmic playing, and practice 3) time management of classroom: lack of basic melodies in songs and time limitation of class learning and 4) other(s): melodic variation, song recitation, and balance controls of music ensemble.